Effect of Knee Extensor Strength on Incident Radiographic and Symptomatic Knee Osteoarthritis in Individuals With Meniscal Pathology: Data From the Multicenter Osteoarthritis Study - Thorlund, Jonas B.; Felson, David T.; Segal, Neil A.; Nevitt, Michael C.; Niu, Jingbo; Neogi, Tuhina; Lewis, Cora E.; Guermazi, Ali; Roemer, Frank; Englund, Martin (Arthritis & Rheumatism-Arthritis Care & Research, 2016)
High knee extensor strength may be important to protect against the development of knee osteoarthritis (OA) in populations at elevated risk, such as individuals with meniscal pathology. We investigated the extent to which high knee extensor muscle strength was associated with a decreased risk of developing radiographic or symptomatic knee OA in individuals with medial meniscal pathology.We studied knees that at the baseline visit of the Multicenter Osteoarthritis Study had medial meniscal pathology but did not have radiographic knee OA (373 knees in 373 participants) or symptomatic knee OA (combination of radiographic knee OA and frequent knee symptoms; 531 knees in 531 participants). Isokinetic knee extensor strength was measured at baseline, and participants were followed for development of incident radiographic knee OA or incident symptomatic knee OA at 84 months. Separate binomial regression analyses with robust SEs adjusted for age, history of knee surgery, physical activity level, and clinic site were conducted for men and women.High knee extensor strength (normalized by allometric scaling) was associated with a reduced risk of radiographic knee OA in women (relative risk [RR] 0.52, 95% confidence interval [95% CI] 0.29-0.94) but not in men (RR 0.56, 95% CI 0.27-1.16). High knee extensor strength did not protect against the development of symptomatic knee OA, either in women or men.The results only partly confirm the hypothesis that high knee extensor muscle strength protects against later development of knee OA in individuals with medial meniscal pathology.
EVALuna2:14635